Black homicide in a midsize southern city, 1980–1989 - Stokes, Larry D. (American journal of criminal justice, 1993)
This study examined homicides from 1980–1989 in a midsize southern city (Chattanooga, Tennessee). More specifically, the study examined the homicide rate as it related to age, gender, and race of both the victim and offender, as well as the type of weapon used.